Deregulated hyaluronan metabolism in the tumor microenvironment drives cancer inflammation and tumor-associated immune suppression - Donelan, William; Dominguez-Gutierrez, Paul R.; Kusmartsev, Sergei (Frontiers in Immunology, 2022)
Hyaluronan (HA) is known to be a prominent component of the extracellular matrix in tumors, and many solid cancers are characterized by aberrant HA metabolism resulting in increased production in tumor tissue. HA has been implicated in regulating a variety of cellular functions in tumor cells and tumor-associated stromal cells, suggesting that altered HA metabolism can influence tumor growth and malignancy at multiple levels. Importantly, increased HA production in cancer is associated with enhanced HA degradation due to high levels of expression and activity of hyaluronidases (Hyal). Understanding the complex molecular and cellular mechanisms involved in abnormal HA metabolism and catabolism in solid cancers could have important implications for the design of future cancer therapeutic approaches. It appears that extensive crosstalk between immune cells and HA-enriched stroma contributes to tumor growth and progression in several ways. Specifically, the interaction of tumor-recruited Hyal2-expressing myeloid-derived suppressor cells (MDSCs) of bone marrow origin with HA-producing cancer-associated fibroblasts and epithelial tumor cells results in enhanced HA degradation and accumulation of small pro-inflammatory HA fragments, which further drives cancer-related inflammation. In addition, hyaluronan-enriched stroma supports the transition of tumor-recruited Hyal2+MDSCs to the PD-L1+ tumor-associated macrophages leading to the formation of an immunosuppressive and tolerogenic tumor microenvironment. In this review, we aim to discuss the contribution of tumor-associated HA to cancer inflammation, angiogenesis, and tumor-associated immune suppression. We also highlight the recent findings related to the enhanced HA degradation in the tumor microenvironment.